On multi-species families: pets as subject of rights in cases of marital dissolution - Silva Galdino Cardin, Valéria; Rodrigues Vieira, Tereza (Revista do Programa de Pós-Graduação em Direito, 2017)
The purpose of this study is to analyze common household pets as subjects of rights, that is, holders of a specific protection that guarantees their well-being within family relationships as members, due to the bonds and affectivity they have developed. In this context, questions are raised as to the possibility of applying, by analogy, the norms of Family Law, specifically with regards to custody, visitation rights and alimony, when there is marital dissolution. For the development of the research, the theoretical method was used, which consists of a bibliographic review and analysis of the country’s legislation.